Sistem Informasi Pelaporan Gangguan Layanan PDAM Berbasis Mobile dan Pemetaan - Via Sukma Cendanie; Yesi Novaria Kunang (JURIKOM (Jurnal Riset Komputer), 2023)
The Lematang Enim Regional Drinking Water Company (PDAM) is a company whose job is to serve customers. The public service in Lematang Enim Regency is reporting disturbances from customers at PDAM by telephone or by going directly to the PDAM service department and will be served by customer service officers by providing a disturbance report form. Then the officer submits a complaint handling warrant to the technical picket officer concerned to be followed up at the intended location. This study aims to design a mobile-based complaint information system and mapping. Making the application using the RAD (rapid application development) method with the stages of analyzing the stages of the required needs, designing the design model to be made, implementing a mobile-based fault reporting information system and mapping to make it easier for customers and technical parties. This research produces a system that can send customer service disruption report data to a server via a mobile-based device. This system can be used by customers and technical staff to the location of the damage and carry out repairs to completion. With this system, it is hoped that it will be able to fulfill the basic needs of PDAM Lematang Enim to improve service to customers and make it easier for customers to submit service interruption reports.